Nedsättande uttryck i ordböcker - Grönros, Eija-Riitta (Nordiske Studier i Leksikografi, 2005)
This article discusses dcrogatory cxprcssions in a monolingua\ cxplanatory dictionary: why is a word labelled as derogatory or insulting, and what types ofwords arc providcd with such \abcls. For cxample, it is common that words rcfcrring to pcoplc considcrcd to be lacking in intelligcncc arc not labcllcd as derogatory. We may think that thcrc is no nccd for a style !abc!, since the definition of thc word already exprcsscs its negative naturc. Yct, thcrc are also words whosc definitions express somcthing negative and insulting and that arc still providcd with a stylc !abc!. What, thcn, is thc diffcrcncc that makes same exprcssions dcrogatory? Words that are labellcd as dcrogatory may also diffcr from cach othcr: in same cascs, thc \abc! is given to dcrogatory namcs for neutral referents, whcrcas in othcrs, thc meaning as such may be dcrogatory. Howcvcr, thc di!Tcrcnt cascs do not diffcr in thc way thcy arc prcscntcd, and wc may ask whcthcr thcy should.